Clinical Profile and Prognostication in Patients Admitted at Medical Intensive Care Unit at B. P. Koirala Institute of Health Sciences - Koirala, Puru; Bhatta, Narendra; Ghimire, Ram Hari; Mishra, Deebya Raj; Bidesh Bista, Bidesh (Birat Journal of Health Sciences, 2020)
Introduction: Critical Care management is an important issue in developing countries where Medical Intensive Care Units (MICU) patients have comorbidity or complications of multisystem involvement. Objectives: The objective of study was to analyze clinical profiles of patients in Medical Intensive Care Unit and identify applicable factors that prognosticate outcomes. Methodology: Study conducted at Medical Intensive Care Unit of B. P. Koirala Institute of Health Sciences, Dharan, Nepal. Records from July 31, 2013 to August 1, 2014 were retrospectively studied. Clinical profiles were analyzed, outcomes defined as improved, referred, Leave Against Medical Advice (LAMA) or death. An online calculator (MD+Calc) was used to calculate Sequential Organ Failure Assessment Score (SOFA). Descriptive statistics were used, values <0.05 were statistically significant. Results: Of 70 patients 36 (51.4%) were female, 30 (42.9%) had sepsis of which 12 (40%) had Community-Acquired Pneumonia. 8 (11.43%) had Acute Respiratory Distress Syndrome, 7 (10%) had congestive cardiac failure. 43 (61.43%) improved, 17 (24.3%) expired, 9 (12.86%) LAMA, one patient was referred. Sequential Organ Failure Assessment Score was >9 in 23 (41.07%) cases. Of 17 expired cases, 14 (82.35%) had SOFA score >9. Conclusion: Sepsis with pulmonary involvement is primary diagnosis in patients requiring Medical Intensive Unit Care. Sequential Organ Failure Assessment Score was useful for prognostication and can be used for better clinical decision-making.